2016
DOI: 10.1590/1982-43272664201612
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Patient, Family and Staff Satisfaction in a Mental Health Service

Abstract: Psychosocial Care Centers (CAPS) provide care to people with psychiatric disorders and aim to reinsert them into the community. Assessing these services is important to maintaining quality. This study assessed the satisfaction level of 84 patients, 84 family caregivers and 67 professionals from a large center of mental health care center (CAPS-III). Structured interviews were individually held by applying the Satisfaction with Mental Health Services Scales (SATIS-BR) and socio-demographic questionnaires. Overa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 22 publications
4
9
0
Order By: Relevance
“…These results are in line with those previously reported in Brazilian studies that evaluated the satisfaction of family members through the SATIS-BR questionnaire and investigated the satisfaction of caregivers of patients assisted in outpatient mental health services. [19][20][21][22][23][24][25] The results also corroborate those found by the National Program of Hospital and Psychiatry Assessment (Programa Nacional de Avaliação dos Serviços Hospitalares -PNASH 2012/2014), in which the hospital where this study was performed received high scores after being evaluated for technical requirements and user satisfaction. 30 Some international studies, however, have found lower rates of family satisfaction.…”
Section: Factors Associated With Family Satisfactionsupporting
confidence: 79%
See 2 more Smart Citations
“…These results are in line with those previously reported in Brazilian studies that evaluated the satisfaction of family members through the SATIS-BR questionnaire and investigated the satisfaction of caregivers of patients assisted in outpatient mental health services. [19][20][21][22][23][24][25] The results also corroborate those found by the National Program of Hospital and Psychiatry Assessment (Programa Nacional de Avaliação dos Serviços Hospitalares -PNASH 2012/2014), in which the hospital where this study was performed received high scores after being evaluated for technical requirements and user satisfaction. 30 Some international studies, however, have found lower rates of family satisfaction.…”
Section: Factors Associated With Family Satisfactionsupporting
confidence: 79%
“…35 Furthermore, in some situations, the satisfaction levels observed are not only related to the quality of services, since high These data suggest that the relatives studied found greater satisfaction regarding the treatment given to the patients, considering that this treatment was necessary to the patient and was helping them to deal more efficiently with their problems. [19][20][21][22][23][24][25] These aspects were also widely cited in qualitative data as factors of higher family satisfaction. However, the 'Privacy and confidentiality' factor, associated with physical conditions and comfort of the service, showed lower levels of satisfaction, and these factors were more often reported when the participants were asked about the aspects that would need to be improved in the units.…”
Section: Factors Associated With Family Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though the importance of considering the perspective of patients when assessing mental health services has been recognized, as has the fact that a satisfaction measure is an indicator of quality, studies assessing levels of patient satisfaction have been unequally conducted (Bandeira & Silva, 2012;Perreault, Rousseau, Provencher, Roberts, & Milton, 2011;Resende, Bandeira, & Oliveira, 2016;Silva, 2014). Patients compose the most frequently addressed group, at the expense of family members and workers (Leal, Bandeira, & Azevedo, 2012;Perreault et al, 2011).…”
mentioning
confidence: 99%
“…Patients compose the most frequently addressed group, at the expense of family members and workers (Leal, Bandeira, & Azevedo, 2012;Perreault et al, 2011). Additionally, there are few studies including multiple perspectives, that is, simultaneously assessing the perspectives of all those involved: patients, families, and professionals, when assessing the same service (Camilo, Bandeira, Leal, & Scalon, 2012;Resende et al, 2016;World Health Organization [WHO], 2001). There are also few studies addressing the factors associated with satisfaction with services using multiple regression analysis.…”
mentioning
confidence: 99%